SISTEM INFORMASI MUTASI PEGAWAI PADA DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN GORONTALO - Wahyudin Hasyim (Universitas Muhammadiyah Gorontalo, 2021)
An information systems of employee mutation is vitally nevessary. Because it is very helpful, facilitate the implementation of the tasks, especially in making the draft of SK teacher mutation or `employee mutation created using by visual basic version 6.0 is software commonly used by programmers to create application for a variety of needs. This application is made simple and completed with an employee database that will be used as a database for employee mutation. The last conclusion of this simple appliccation is expected to simplify the work creating a draft decree of employee mutation because it is supported by a database that is maintained.